Using Mindomo to Engage Students in Higher-Order Thinking - Sabourin, Brandon M. (Compass: Journal of Learning and Teaching in Higher Education, 2020)
Mindomo (www.mindomo.com) is a web-based tool designed to aid in the creation of digital concept maps. This article provides an overview of concept mapping and Mindomo followed by reflections on implementing Mindomo in a digital technology course for pre-service teachers. A SWOT analysis of Mindomo is presented in concept map format, with the goals being to provide information helpful to anyone considering using Mindomo and to encourage instructors to consider how concept mapping might facilitate higher-order thinking in their classes.